Conflict And Moral Values Of Being That Found In “Kung Fu Panda 1” Movie - Ming, Adrian; Gde Nova Winarta, I.B. (BULLET : Jurnal Multidisiplin Ilmu, 2023)
This study is aimed to find out the conflict that found in the Kung Fu Panda 1 movie, and to analyze the moral values of being that found in the Kung Fu Panda 1 movie. This movie narrates about a fat panda who has a solid desire about being the greatest warrior. The descriptive qualitative method was used in this research to elaborate the conflict in this movie also, deliver a clear and brief description of the moral values of being. In the data collection, researcher combining between watching and recording techniques. These things are examined using DiYanni (2000) theory to analyze the conflict, and while, Linda and Eyre (1993) to identify the moral values of being in the movie. The subject of this research is the movie entitled Kung Fu Panda 1 by Ethan Reiff and Cyrus Voris. The result of this study showed that are three types of conflict that found in the Kung Fu Panda 1 movie, namely between character and themselves, between character and the other characters, and between character and society. Furthermore, there are five types of moral values of being, namely honesty, courage, peaceability, self-reliance and potential, and self-discipline and moderation.